Beyond Marxist Economism and Entrepreneurial Essentialism: Post-Colonial Politics of Empire in Chinua Achebe’s And Linus Asong’s Writings - Ndi, Alfred (Journal of Social Economics Research, 2014)
This paper on political economy of entrepreneurship draws insights from creative writings of Chinua Achebe and Linus Asong to argue that, contrary to Marxist optimisms and idealisms, the business of political entrepreneurship is so complicated because it intersects with multiple conflicting narratives. These narratives of empire take new different and often times contradictory directions such as neo-pariarchalism, the popularity of anarchism, limitations of the intelligentsia class. religion as substitution, issues of feminist labour power and social class questions.